Corporate governance in Malaysian tourism small and medium-sized enterprises: review of research issues - Zainol Abidin, Azlan; Mohd Shariff, Nurhazani; Ibrahim, Mohd Azhar; Yusof, Noor Suhaila (INSInet Publications, 2016)
Background: Tourism small and medium-sized enterprises (SMEs) currently emerge as one of the world’s major enterprises with significant changes in its structure and operation. As for Malaysia, the continuous efforts to stimulate the tourism industry by the Malaysian government have created a positive effect on the business activities of SMEs.However, many studies emphasize the problems in managing SMEs in terms of corporate governance for instance lack of awareness on corporate governance structure, lack of awareness on corporate governance operation, size of the board, lack of industry expertise and strategic vision. Objective: This paper presents a general review of the research issues regarding the matter as the first step to enhance further research. Results: The review from related articles indicated that there are three major research issues on corporate governance in SMEs which can also be discussed in the tourism industry.These issues were identified as the roles of corporate governance, the challenges of corporate governance and the significance of corporate governance to SMEs. Conclusion: These three issues should be given serious attention by scholars in determining specific area to be investigated within the context of tourism SMEs.Further, the issues also contribute in terms of practicing corporate governance toward managing tourism SMEs effectively.